People's Consumptive Behavior on the Reaction of Government Regulation to Fuel Price Increase - Rizqi Fitrianti; Ita Rosita Wahyiah (LEGAL BRIEF, 2022)
The adjustment to the fuel price increase occurred again, this is the second time President Joko Widodo has made this policy. Various reactions that occur in society related to massive information in the media make various behavior changes that are quite significant. Among them are consumptive behaviors to obtain excessive products outside the main needs. The problem discussed in this study is the reaction caused by the exposure of information on a government policy. As well as feedback in the form of follow-up communication in the form of changes in community behavior and the phenomenon of rapid reactions that occur to these stimulants (news of fuel increases). This study aims to analyze the reaction of public behavior to the actions made by the government, in the form of fuel price increase policies, based on the S-R (Stimulus - Response) communication model. The method used in this study is an ethnographic method with a qualitative approach. The ethnographic method is carried out for the analysis of sociocultural life in the form of community behavior individually and in groups according to local culture. From this research, it can be concluded that government regulations set as government policies for adjusting fuel price increases can cause reactions in the community. The S-R communication model can show that the action of information in the media that the communicant receives as an organism, can give rise to a variety of direct reactions in return. Such as long queues and panic buying behavior.